Undergraduate students' perceptions on utilizing Deepseek AI as a tool in writing journal articles - Aisyah Rizqa Fitri Siregar; Benni Ichsanda Rahman Hz (University of Muhammadiyah Malang, 2025)
In the ever-evolving digital era, artificial intelligence technologies such as DeepSeek AI are widely used by academics as a solution to writing challenges, especially among students who still develop their academic writing skills. This study aimed to deeply understand undergraduate students' perceptions of the advantages and disadvantages of using DeepSeek AI as a tool in the process of writing scientific journal articles. This study used a qualitative approach with a case study design involving ten students from various educational majors who had used DeepSeek AI in the process of writing scientific journals. 10 participants were selected through purposive sampling based on specific criteria, including prior experience using DeepSeek AI in academic writing. Data were collected through a questionnaire with a Likert scale and semi-structured interviews to capture perceptions in more depth. The results showed that most students felt real benefits from using DeepSeek AI, especially in helping to generate initial ideas when experiencing writer's block, structuring writing more systematically, and improving technical aspects such as grammar and scientific writing style. This study emphasized the importance of using technology wisely in the context of higher education, as well as the need to strengthen information literacy and critical thinking skills in the digital era. Thus, DeepSeek AI is potential to be an effective tool in supporting the learning process, as long as it is used in a balanced manner and does not replace the important role of humans in thinking and writing scientifically.